Development of a curriculum framework to facilitate critical thinking skills of undergraduate students in developing countries : a multi-method study of a Ghanaian nursing educational institution - Boso, Christian Makafui (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.